Modified full-face snorkeling mask for thoracic surgery and otolaryngology surgical use: comfort and usability assessment during the COVID-19 pandemic: Modified full-face snorkeling mask for surgical use in otolaryngologic and thoracic surgery - Cacco, Tommaso; Fragale, Marco; Sampieri, Claudio; Castello, Eolo; Risso, Carlo; Piras, Maria Teresa; Durando, Paolo; Montecucco, Alfredo; Pariscenti, Gian Luca; Peretti, Giorgio (La Medicina del Lavoro, 2021)
Background: A worldwide personal protection equipment (PPE) shortage has emerged during COVID-19 pandemic, contributing to the high incidence of SARS-CoV-2 infection among health care providers. To address this lack of PEE, new solutions have been researched. Among those, full-face snorkeling masks demonstrated to be an interesting option. Among surgical specialties otolaryngologists and thoracic surgeons are at high risk of infection, due to the close contact with airway secretions. Objectives: We tested the comfort and usability of a modified full-face snorkeling mask (Ocean Reef Mask Aria QR+) as a protective device for otolaryngologic and thoracic surgeries. Methods: The mask was customized with a 3D-printed adaptor supporting many industrial filter types, including FFP3 and heat and moisture ex- changers (HME). We evaluated surgical performances of the mask, both subjectively, with a questionnaire filled in by the surgeons, as well as objectively, monitoring transcutaneous PCO2 and PO2 values of surgeons during surgical procedures. Results: The modified full-face snorkeling mask was tested during 9 otolaryngologic and 15 thoracic surgery procedures. The device demonstrated very good overall vision quality with some limitations regarding lateral vision and almost no difficulties in usability. Water condensation into the mask was absent in almost every case. Both PO2 and PCO2 param- eters remained within normal ranges during every procedure. Discussion: The modified full-face snorkeling mask can be an innovative PPE. In the current COVID-19 pandemic scenario, the worldwide shortage of protective masks and goggles may exploit this ready-to-use and low-cost solution, especially for high-risk surgical procedures.